Kollektív emlékezet és történeti tudományok - S. Varga, Pál (Studia Litteraria, 2012)
The modes of relating to the past move between two poles: first, the Cartesian model of cognition, where subject and object are opposed to each other; and second, „the preliminary understanding of being,” i.e., conceiving of the past as existential experience. Accordingly, the scientific nature of historical knowledge is based on the verifiability of knowledge as such, while the collective function of memory is founded on the actually relevant existential meaning of the past, often originating in claims that go against historical science. Historical research cannot ignore reflecting on its own subject even if it sets out to understand our „being in” the past. At the same time, the self-reflexivity of history as science is limited by the fact that the researcher as a subject is included in the continuity of history, creating his/her reflected knowledge on the basis of testimonies by non-reflective participants. Moreover, this knowledge can only be verbalized by relying upon narrative structures, by using various rhetorical and poetical strategies. On the other hand, collective memory cannot be knowledge based merely on existential experience, because the past that is not personally experienced can only be attained by learning, and this is influenced by historical education based on scientific results. The validity of the memorial knowledge of one’s own community is limited by the countermemory of contact communities. History studies (including mnemohistory) usually claim to have influenced collective memory. However, this ambition can only be justified if it does not start out from its own truths but the need for a relevant and actual interpretation of collective memory.